Investigation of Wolbachia spp in Some Flies Species (Order: Diptera) by PCR - Saki, Cem Ecmel; Simsek, Sami (Kafkas Univ, Veteriner Fakultesi Dergisi, 2014)
Wolbachia is a gram negative intracellular parasite from Rickettsia family which is located into reproductive organs of arthropods and transmitted by horizontally and vertically. The aim of this study was to investigate of Wolbachia spp. in different species of flies by PCR. For this aim, 33 females and 15 males of Musca spp., 30 females and 7 males of Lucilia sericata, 16 females and 4 males of Calliphora vicina, 1 female and 4 males of Sarcophaga haemorrhoidalis and 27 females and 10 males of Chrysomia albiceps adult flies were used. After the isolation of genomic DNA, the specific primers were used and PCR was performed for the amplification of Wolbachia wsp (Wolbachia surface protein) gene. As a result, the positive control sample yielded 630 bp band while negative control and none of the tested samples yielded band. In conclusion, Wolbachia spp has been molecularly investigated in some Diptera populations for the first time in Turkey.
Bazi{dotless} sinek (Dizi: Diptera) türlerinde Wolbachia spp'nin PZR ile araşti{dotless}ri{dotless}lmasi{dotless}
Keywords: Musca; Lucilia; Chrysomia; Calliphora; Sarcophaga; Wolbachia; PCR